Josepha Maréchala badania nad psychologią doświadczenia mistycznego a problem empirycznego determinizmu - Bańka, Aleksander (Folia Philosophica, 2018)
The paper deals with the issue of the studies on mystical experience led in first half of 20th century by Joseph Maréchal, Belgian philosopher and the creator of transcendental Thomism. His most important work in this area is "Studies in psychology of mystics" ("Études sur la Psychologie des Mystiques"), first volume of which was published in 1924. Maréchal’s research, apart from the attempt made to specify the nature of mystical experience on the basis of the concept of the dynamic purpose of intellect and on the problem of so-called sense of presence, concerned also some methodological issues. Making use of his background in biology and psychology, Maréchal focused on the question of the possibility of applying the methods of empirical sciences in psychology of mystical experience. This was first of all aimed at application of those methods to analysing both special phenomenon related to mystical experience and its essential hidden depth. This paper aims at showing how Maréchal, using the tools of philosophers, evaluates the possibility of using scientific methods to study phenomenological and criticises some deterministic presuppositions underlying those methods.